Translating Indonesian to English: Problems and Solutions Experienced by English Education Students - Idami, Zahratul; Keumala, Meta; Saifani, Meutia; Nadila, Evi; Dakiani (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2025)
This study investigates the challenges faced by students in translating Indonesian to English, focusing on students from the English Education Department at IAIN Langsa who had enrolled in the Scientific Translation course. A descriptive qualitative methodology was employed, with five students as the participants. Data were collected through documentation analysis and interviews. The research reveals four key problems in translation, including achieving equivalent meaning, determining particular terminology, dealing with idiomatic expression, and addressing mechanical errors especially punctuation. The study also explored potential solutions and strategies that students could employ to improve their translation skills such as consulting bilingual dictionary, using translation mechines (google translate and DeepL), and discussing with friends and lecturer. The findings provide valuable insights into the specific challenges faced by translation students and suggest areas for further improvement in translation training within the English Department.